2003
DOI: 10.1177/016264340301800201
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Video-Based and Applied Problems on the Procedural Math Skills of Average- and Low-Achieving Adolescents

Abstract: The purpose of this study was to investigate the effects of video-based, anchored instruction and applied problems on the ability of 11 low-achieving (LA) and 26 average-achieving (AA) students to solve computation and word problems. A repeated-measures design with staggered baselines was used to compare the performance of two groups of LA students and one group of AA students across three instructional conditions: (a) baseline instruction, (b) anchored instruction, and (c) instruction with applied problems. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
43
0
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(46 citation statements)
references
References 37 publications
2
43
0
1
Order By: Relevance
“…Because the design of the study included periods of typical instruction, we cannot be sure how much of this improvement, if any, can be attributed to EAI. Although there has been some evidence to suggest computation instruction embedded in EAI may have important benefits (e.g., Bottge, Heinrichs, Chan, Mehta, & Watson, 2003; Cohen, Bottge, & Wells, 2001), it is not possible to disentangle the instruction‐by‐performance effects in this study. All that can be stated with cautious optimism is that some students in both sequences improved their computation scores by participating in the combination of EAI and typical curricula.…”
Section: Discussionmentioning
confidence: 90%
“…Because the design of the study included periods of typical instruction, we cannot be sure how much of this improvement, if any, can be attributed to EAI. Although there has been some evidence to suggest computation instruction embedded in EAI may have important benefits (e.g., Bottge, Heinrichs, Chan, Mehta, & Watson, 2003; Cohen, Bottge, & Wells, 2001), it is not possible to disentangle the instruction‐by‐performance effects in this study. All that can be stated with cautious optimism is that some students in both sequences improved their computation scores by participating in the combination of EAI and typical curricula.…”
Section: Discussionmentioning
confidence: 90%
“…For students with a learning disability, video‐based interventions were studied in small numbers for teaching mathematics. For example, Bottge and associates successfully used contextualized instruction within videos (i.e., anchored instruction) to teach secondary students with a learning disability problem solving (Bottge, ; Bottge, Heinrichs, Mehta, & Hung, ), pre‐algebra (Bottge, Heinrichs, Chan, & Serlin, ), and geometry (Bottge, Heinrichs, Chan, Mehta, & Watson, ). More recently, Bottge et al.…”
Section: Strategies For Teaching Students With Learning Disabilitymentioning
confidence: 99%
“…Previous research has demonstrated that latent groups of students can be identified that differ in the kinds of cognitive strategies they use to answer test questions (Embretson & Reise, 2000;Rost, 1990Rost, , 1997. In this application, an LTA-MRM was used in the assessment of effects of a multiwave experiment of an EAI instructional treatment (Bottge, Heinrichs, Chan, Mehta, & Watson, 2003) on mathematics achievement of LD and non-LD middle school students. If EAI instruction is effective at improving LD students' mathematics test performance on items requiring complex skills, then they should be better able to correctly answer these items following EAI instruction than before.…”
Section: Application: Effects Of Enhanced Anchored Instruction On Matmentioning
confidence: 99%